Analisis Sharia Compliance pada Sistem Jual Beli, Simpan, dan Cetak Emas Antam Berbasis Aplikasi Online Tamasia - Maulidia Sakinah; Nur wahidin; Muhammad Zilal Hamzah (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2022)
This study pursuits to determine how the system and technique of trading, saving, and printing Antam's gold mechanism in sharia through the online application Tamasia beneath the auspices of PT. Tamasia Global Sharia. To discover what contracts have been recognized as being used in buying, selling, and saving Antam's gold thru the Tamasia online application and whether or no longer these contracts are according with the related DSN-MUI Fatwa. This study uses descriptive qualitative method research with a normative juridical research approach and empirical juridical research with the aid of analyzing Tamasia products. The evaluation and identification of the facts acquired was juxtaposed with the regulation of sharia principles, specifically the DSN-MUI fatwas related to the contracts used. The outcomes confirmed that based on an analysis of the general provisions that became the substance of the related DSN-MUI fatwas, the recognized contracts used in the buying and selling mechanism and saving of Antam's gold through the Tamasia online application included wadi'ah yad amanah contracts on gold savings. that is saved inside the application for the buy Suka-Suka product, and the salam contract in the system of ordering Antam's gold bars for savers who desire to withdraw their gold savings balance. Keywords: Gold, Online Applications, Wadi'ah, Salam.